Estimation of errors in determination of main parameters of earthquake hypocenter, recorded by the national seismic network of Vietnam - Lu, Ngo Thi; Yu., Burmin V.; Hang, Phung Thi Thu; Hoan, Vu Thi; Giang, Ha Thi (Vietnam Journal of Earth Sciences, 2018)
In this paper the authors present the error estimation in determining main parameters of earthquake hypocenter based on solving the system of linear equations, expressing the relationship between earthquake coordinates and the coordinates of the seismic stations. The results of the error estimation in determining the epicenter coordinates and the focus depth of the earthquakes recorded by the system of 30 seismic stations in Vietnam are presented, interpreted and compared with the results of the previous studies. The results show that the operation of the seismic network of Vietnam is not really optimal, particularly when determining the epicenter coordinates and the focus depth of the earthquakes in the East Vietnam Sea region. The national seismic network of Vietnam allows determination of the epicenter coordinates and the focal depth of earthquakes for most of the Vietnam territory with the errors ∆h ≤ 20 km, ∆φ ≤ 4 km, ∆ ≤ 5 km. The errors of the determination of the epicenter coordinates and the focal depth of the earthquakes are increasing to the south and southwest areas of the territory of Vietnam and reach the maximum in these areas. Particularly, errors of the determination of the epicenter coordinates (∆φ, ∆λ) and the focal depth (∆h) of earthquakes increase very rapidly toward the East Sea of Vietnam and reach the maximum in the region between the longitudes of 116-118°E. The Vietnam seismic network allows determining the epicenter coordinates and the focal depth of earthquakes in the Northern Vietnam with the smaller errors than in Central and Southern Vietnam, and this fact proves that the distribution of seismic network in Northern Vietnam is more optimal than the station networks in the Central and Southern Vietnam. Therefore, in order to improve the effectiveness of the Vietnam seismic network, more seismic stations need to be added to the Central and Southern Vietnam. References Aranovich Z.I., 1980. On the method of selecting the optimal positions of seismic stations in the local network. //Methodologies and assessment results of the effectiveness of the regional seismic network. Tbilisi: Mesnhiereba, 150-157 (in Russian). Aranovich Z.I., Akhalbedasvili А.М., Gosadze О.D. et al., 1977. The methodologies of evaluating the effectiveness of regional seismic network, in case of the Caucasus region.//The issues of optimization and automation of seismic observations. Tbilisi: Mesnhiereba, 27-57 (in Russian). Bui Van Duan, Nguyen Cong Thang, Nguyen Van Vuong, Pham Dinh Nguyen, 2013. The magnitude of the largest possible earthquake in the Muong La-Bac Yen fault zone. J. Sci. of the Earth, 35, 53-49. Burmin V. Yu., 1976. The task of experimental planning and the estimation of the system of linear algebraic equations.//The USSR Academy of Sciences Publishing House. Cybernetics, 2, 195-200. Burmin V. Yu., 1986. The optimal distribution of seismic stations when recording near earthquakes.//The USSR Academy of Sciences Publishing House. Geophysics. Moscow, 5, 34-42 (in Russian). Burmin V. Yu., Akhmechiev V.M., 1994. The errors in determining parameters of near earthquake hypocenter and the effectiveness of seismic network.//Journal of Volcanology and Seismology. Moscow, 2, 109-128 (in Russian). Burmin V. Yu., Ngo TL., Kondorskaia N.V. and Akhmechiev V.M., 1992. The geometric analysis of existing seismic network in the Northern Vietnam.//The news from Russian Academy of Sciences. Journal of Geophysics. Moscow, 6, 123-128 (iIn Russian). Burmin V. Yu., Ngo T.L., Tran V.P., 2009. Estimation of efficiency of seismic stations modern network and design of an optimal one on the territory of Vietnam.// Journal “Seismic Instruments”, 45(1), 27-35. Burmin V. Yu., Nguyen VP., 2001. Planning to optimum regional network of the seismological observations for South- East Asia.//Journal “Volcanology and Seismology”, 1, 68-75. Iosif T. and Iosif S., 1974. Optimization of seismic stations distribution in Romania.//Studii si cercetari de geofisica, 12, 51-88. Iosif T., Skoko D. and Sato Y., 1972. Optimum distribution of seismic stations in Romania.//Bull. Int. seism. Earthq. Eng, 9, 121p. Kijko A., 1975. On optimal extensions of regional networks of seismic stations - Publs. Inst. Geophys. Pol. Acad. Sci., 96, 57-119. Kijko A., 1978. Method of the optimal planning of regional seismic networks.//Polish Academy of Sci. publication of the inst. Of geoph. A-7 (119). Panctwowe wydawnictwo naukowe. Warszawa; Lodz, 63p. Kijko A., 1980. Optimum seismic networks in the Ostrova coal basin.//Czechoslovakia. Acta montana UGG CSAV. Praha, 55, 73-95. Marshall A.W., Olkin I., 1965. Norms and inequalities for condition numbers.//Pacific J. Math, 15, 241-247. Marshall A.W., Olkin I., 1969. Norms and inequalities for condition numbers.//Linear Algebra and Application, 2(2), 167-172. Marshall A.W., Olkin I., 1973. Norms and inequalities for condition numbers.//Linear Algebra and Application, 3(7), 191-300. Ngo TL., 1990. Kinetic and dynamic parameters of earthquake hypocenter in the Northern Vietnam. The Candidate of Sciences Thesis on Mathematics-Physics, Speciality Geophysics. Institute of Geophysics, the USSR Academy of Sciences. Moscow, 133p (in Russian). Ngo T.L., 1999. The characteristics of seismicity and the main features of earthquake hypocenter in the Southeast Asia from the viewpoint of clarifying the new tectonic structures. The Doctor of Science Thesis on Mathematics-Physics, Speciality Geophysics. Institute of Geophysics, the USSR Academy of Sciences. Moscow, 342p (in Russian). Ngo T.L., 2005. The algorithm for improvement of velocity model of Earth’s crust and hodographs of travel times of seismic waves in the territory of Vietnam. J. Sci. of the Earth, 27(1), 23-26. Ngo T.L., 2005. The analysis of the seismic data for accounting hodographs of travel times of P-wave. J. Sci. of the Earth, 27, 374-377. Ngo T.L., Tran V.P., Vu T.H., Le T.T., 2014. The establishment of velocity model and hodographs of travel times of seismic waves in the Earth’s crust in the Northern, Central and Southern regions of Vietnam. Journal of Geology, Hanoi, Series A, 341-345, 355-365. Nguyen Quy Hy, et al., 1979. Optimal addition of seismic network in the Vietnam territory by the method of seismic experimental planning.//The research results of “Earth Sciences” 1977-1978. Series Geophysics. Vietnam Academy of Science and Technology. Hanoi, 9-31 (in Vietnamese). Nguyen Van Hung., Hoang Quang Vinh, Nguyen Van Huong, 2016. Tectono-structural system and geodynamic features of Northwest Vietnam in the late Cenozoic period. Vietnam J. Earth Sci., 38(1), 38-45. Doi: 10.15625/0866-7187/38/1/8408. Sato Y., 1965. Optimum distribution of seismic observation points.//Zisin J. Seism. Soc. Japan, 18(1), 9-14. Sato Y., Skoko D., 1965. Optimum distribution of seismic observation points II.//Bull. Earthquake. Res. Inst., 43(3), 451-458. Sato Y., Ochi I., 1967. Accuracy of the determination of earthquake source parameters in and around Japan.//Bull. Earthq. Res. Inst., 45(1), 1-17. Savarenski E.F., Shafronov V.V., Peskov A.B. et al., 1979. Optimal planning of seismic stations from the viewpoint of minimizing error in the epicenter determination.//The USSR Academy of Sciences Publishing House, 8, 64-71 (in Russian). Skoko D., Kotake Y., Sato Y., 1968. Optimum distribution of seismic observation points. V//Bull. Earthquake. Res. Inst., 46(4), 821-840. Skoko D., Sato Y., Ochi I., Dutta T.K., 1966. Accuracy of the determination of earthquake source parameters as determined by Monte Carlo method: Observation on Indian Network.//Bull. Earthquake. Res. Inst., 44(3), 893-900.